Experimental evidence that novel land management interventions inspired by history enhance biodiversity. Issue 5 (22nd January 2021) - Hawkes, Robert W.; Smart, Jennifer; Brown, Andy; Jones, Helen; Lane, Steve A.; Lucas, Colin; McGill, James; Owens, Nick; Ratier Backes, Amanda; Webb, Jon R.; Wells, Doreen; Dolman, Paul M.
Abstract: To address biodiversity declines within semi‐natural habitats, land management must cater for diverse taxonomic groups. Integrating our understanding of the ecological requirements of priority (rare, scarce or threatened) species through 'biodiversity auditing', with that of the intensity and complexity of historical land use, encourages novel forms of management. Experimental confirmation is needed to establish whether this enhances biodiversity conservation relative to routine management. Biodiversity auditing and historical land use of dry‐open terrestrial habitats in Breckland (Eastern England) both encourage management incorporating ground disturbance and spatio‐temporal variability. To test biodiversity conservation outcomes, we developed forty 4‐ha management complexes over three successive winters, of which 20 were shallow‐cultivated (rotovation) and 20 deep‐cultivated (ploughing), stratified across 3, 850‐ha of closed‐sward dry grassland and lowland heathland (collectively 'dry grassland'). Complexes comprised four 1‐ha subtreatments: repeat‐cultivation, first‐time cultivation, 1‐year‐old fallow and 2‐year‐old fallow. We examined responses of vascular plants; spiders; true bugs; ground, rove and 'other' beetles; bees and wasps; ants; and true flies on treatment complexes and twenty‐one 4‐ha untreated controls. Sampling gave 132, 251 invertebrates from 877 species and 28, 846 plant observations from 167 species. Resampling and rarefaction analyses showed shallow‐ and deep‐cultivation both doubled priority species richness (pooling subtreatments within complexes) compared to controls. Priority spider, ground beetle, other beetle and true bug richness were greater on both treatments than controls. Responses were strongest for those priority dry‐open habitat associated invertebrates initially predicted (by biodiversity auditing) to benefit from heavy physical disturbance. Assemblage composition (pooling non‐priority and priority species) varied between subtreatments for plants, ants, true bugs, spiders, ground, rove and other beetles; but only 1‐year‐old fallowed deep‐cultivation increased priority richness across multiple taxa. Treatments produced similar biodiversity responses across various dry grassland 'habitats' that differed in plant composition, allowing simplified management guidance. Synthesis and applications . Our landscape‐scale experiment confirmed the considerable biodiversity value of interventions inspired by history and informed by systematic multi‐taxa analysis of ecological requirements across priority biota. Since assemblage composition varied between subtreatments, providing heterogeneity in management will support the widest suite of species. Crucially, the intended recipients responded most strongly, suggesting biodiversity audits could successfully inform interventions within other systems. Abstract : Our landscape‐scale experiment confirmed the considerable biodiversity value of interventions inspired by history and informed by systematic multi‐taxa analysis of ecological requirements across priority biota. Since assemblage composition varied between subtreatments, providing heterogeneity in management will support the widest suite of species. Crucially, the intended recipients responded most strongly, suggesting biodiversity audits could successfully inform interventions within other systems.